Design and Rationale for Common Data Elements for Clinical Research in Pediatric Critical Care Medicine. Issue 11 (November 2020) - Ward, Shan L.; Flori, Heidi R.; Bennett, Tellen D.; Sapru, Anil; Mourani, Peter M.; Thomas, Neal J.; Khemani, Robinder G.
Abstract : Objectives: Common data elements are a combination of a precisely defined question paired with a specified set of responses. Common data elements contribute to the National Institutes of Health–supported principle of Findable, Accessible, Interoperable, and Reusableness of research data. Routine use of Common data elements and standardized definitions within pediatric critical care research are likely to promote collaboration, improve quality, and consistency of data collection, improve overall efficiency of study or trial setup, and facilitate cross-study comparisons, meta-analysis, and merging of study cohorts. The purpose of this Pediatric Critical Care Medicine Perspective is to establish a road map for the development of multinational, multidisciplinary consensus–based common data elements that could be adapted for use within any pediatric critical care subject area. Methods: We describe a multistep process for the creation of "core domains" of research (e.g. patient outcomes, health-related conditions, or aspects of health) and the development of common data elements within each core domain. We define a tiered approach to data collection based on relevance of each common data element to future studies and clinical practice within the field of interest. Additionally, we describe the use of the Delphi methods to achieve consensus of these common data element documents using an international, multidisciplinary panel of experts.